Analisis Peluang Perkawinan Beda Agama di Indonesia Pasca Penerapan SEMA No. 2 Tahun 2023 - Ekik Filang Pradana (SAKINAH: Jurnal Hukum Keluarga Islam, 2024)
Abstract: As a progressive step to provide a legal explanation for the problem that has always been discussed with the aim of closing the space for interfaith marriages, the Supreme Court issued Supreme Court Circular Letter No. 2 of 2023 as an answer to the serious problem of interfaith marriages. This research will analyze how the strength of SEMA No. 2 of 2023 in the legal certainty of marriage registration and analyze the opportunities for interfaith marriages after SEMA No. 2 of 2023 in the Supreme Court. The research is a normative legal research using statute approach. It is found that SEMA No. 2 of 2023 provides legal certainty, because of its binding nature; while with regard to the opportunity for interfaith marriages in the Supreme Court and the judicial institutions under it no longer exists, due to the issuance of SEMA No. 2 of 2023. Keywords: Opportunity; Intermarriage; SEMA No. 2 Tahun 2023   Abstrak: Sebagai langkah progresif untuk memberikan penjelasan hukum atas masalah yang selalu diperbincangkan dengan tujuan menutup ruang gerak perkawinan beda agama, Mahkamah Agung menerbitkan Surat Edaran Mahkamah Agung No. 2 Tahun 2023 sebagai jawaban atas masalah serius tentang perkawinan beda agama. Penelitian ini akan menganalisis  bagaimana kekuatan SEMA No. 2 Tahun 2023 dalam kepastian hukum pencatatan perkawinan dan menganalisis peluang perkawinan beda agama pasca SEMA No. 2 tahun 2023 di Mahkamah Agung. Penelitian merupakan penelitian hukum normatif dengan menggunakan pendekatan perundang-undangan (statute approach). Dalam hasilnya ditemukan bahwa SEMA No. 2 Tahun 2023 memberikan kepastian hukum, karena sifatnya yang mengikat; sedangkan  berkaitan dengan peluang perkawinan beda agama di Mahkamah Agung dan lembaga peradilan di bawahnya sudah tidak ada, karena terbitnya SEMA No. 2 Tahun 2023. Kata Kunci: Peluang; Perkawinan Beda Agama; SEMA No. 2 Tahun 2023